(3fbP GdfbhO aj eYQaI GdhLhOs - (3MjOQ Hf Ydj Hf MjOQ GdYdhqj GdMSfj GdBedj, HgGA GdOjf GdWHQj GdbGTj,HYO (B782 (3g`s; (3GdGedj , MjOQ Hf Ydj Hf MjOQ, HgGA GdOjfs
(3ChdgG (B:s
(3GdMeO ddg GdPi JfRg Yf GdcKQI CeG HYO adeG aQZfG ef QSGdI GdhLhO heG GTJed YdjgG hef GdeYGQVI Hjf GdeJcdejf GdJeS ef HYV GNhGfi Gf GfJNH efgG GfJNGHkG eNJUQkG s
(3BNQgG (B:s
(3GdPi gh eTGQ ai UhQI GdGfSGf GdcGed GdPi jJUd HChdi GdhLhO hfSHJg GdjfG ef Gddg gPg BNQ cdGe hBNQ GdGfJNGH GjVG hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3Je ebGHdI GdfSNI Ydi GdCUd Gdefbhdg efgs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
Keywords: (3GdJhMjO hGdedd hGdfMds